HUBUNGAN KEPERCAYAAN DIRI DENGAN KECEMASAN MAHASISWA KEPERAWATAN ANESTESIOLOGI DALAM MENYELESAIKAN SKRIPSI PADA MASA PANDEMI COVID-19 DI YOGYAKARTA - Nia Handayani; Feni Fanika Sari (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2023)
The Covid-19 pandemic affected the whole world, including Indonesia. The central and regional governments provided online learning policies for school and college children to minimize the spread of Covid-19. This situation caused psychological stress including anxiety in Anesthesiology Nursing students who were finishing their thesis. The study aimed to find out the factors related to the anxiety of Anesthesiology Nursing students in completing their thesis during the Covid-19 pandemic in Yogyakarta. This research employed quantitative correlation with a cross-sectional approach. The samples were 119 respondents. The research instrument used the HARS anxiety questionnaire and the RSES self-confidence questionnaire. The results of statistical tests using Spearman Rank found that there was a relationship between self-confidence and anxiety with a p value 0.000. Self-confidence were related to the anxiety of Anesthesiology Nursing students in completing thesis during the Covid-19 pandemic in Yogyakarta.